2021
DOI: 10.26603/001c.18705
|View full text |Cite
|
Sign up to set email alerts
|

Hip and Groin Injury Prevention in Elite Athletes and Team Sport – Current Challenges and Opportunities

Abstract: Hip and groin injury (HAGI) has been reported as a source of significant time loss in elite sport. Field and court-based sports such as basketball, football, hockey, soccer, among others, require explosive multiplanar movement in single stance and high-speed change of direction. Often situations arise where sub-optimal pre-season training has occurred or congested in-season competition minimizes physiologic recovery periods between bouts of physical activity, both of which could magnify concomitant existing ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In the current study, soccer players showed the highest prevalence of groin pain (32.5%) among the team sports examined. Soccer involves a regular combination of kicking and change of direction that may explain this higher incidence of groin injuries [35, 40]. Orchard et al [29] reported that the sport with the highest rates of groin pain was non‐professional men’s soccer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, soccer players showed the highest prevalence of groin pain (32.5%) among the team sports examined. Soccer involves a regular combination of kicking and change of direction that may explain this higher incidence of groin injuries [35, 40]. Orchard et al [29] reported that the sport with the highest rates of groin pain was non‐professional men’s soccer.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Doha agreement meeting on terminology and definitions in groin pain in athletes, the classification system includes defined clinical entities as follow: adductor‐, iliopsoas‐, inguinal‐, pubic‐, and hip‐related groin pain [11, 52]. The increased demands and training loads on athletes combined with individual risk factors may contribute to groin injuries [24, 30, 40]. Groin pain can affect both player and team performance and sometimes can be a career‐ending injury [15, 40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate the risk of musculoskeletal injuries and improve overall performance, it is important to understand the relationship between basketball performance and advanced analytics [35]. Advanced analytics have become an increasingly important tool in the field of sports performance and injury prevention [36].…”
Section: Aim and Objectivesmentioning
confidence: 99%
“…Financial aspects are equally critical; unplanned absences due to injuries can lead to significant financial losses for NBA franchises. This study explores how Data Science and Sports Analytics can mitigate these risks by providing deeper insights into player health and strategic game management [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%